2020
DOI: 10.1111/sdi.12880
|View full text |Cite
|
Sign up to set email alerts
|

Uncertainties in BP management in dialysis patients

Abstract: Hypertension in dialysis patients is extremely common. In this article, we review the current evidence for blood pressure (BP) goals in hemodialysis patients, and consider the effectiveness of interventions by which BP may be lowered, including manipulation of dietary and dialysate sodium; optimization of extracellular water; prolongation of dialysis time; and antihypertensive medication. Although two meta-analyses suggest lowering BP using antihypertensive drugs might be beneficial in reducing cardiovascular … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 154 publications
(206 reference statements)
0
4
0
Order By: Relevance
“…Many studies have consistently shown a J-shaped relationship between mortality and lowest and highest BP in CKD G5D patients [ 32 ]. This relationship also applies to PD patients, without exception [ 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…Many studies have consistently shown a J-shaped relationship between mortality and lowest and highest BP in CKD G5D patients [ 32 ]. This relationship also applies to PD patients, without exception [ 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…Beta blockers, RAAS-blocking agents, and dihydropyridine calcium channel blockers are all reasonable choices. Diuretics may be used in the patients to help fluid removal in those individuals with residual renal function 28 ( Table 1 ).…”
Section: Methodsmentioning
confidence: 99%
“…Decreasing salt consumption leads to decreased blood pressure in the overall population, individuals with high blood pressure from all ethnic backgrounds, individuals with and without diabetes, and patients with chronic kidney disease (CKD) [38][39][40][41][42].…”
Section: Non-pharmacological Interventionmentioning
confidence: 99%